674. Evaluation of the Access Bio CareStart™ Rapid SARS-CoV-2 Antigen Test in Asymptomatic Individuals Tested at a Community Mass-testing Program in Western Massachusetts. (4th December 2021) - Matias, Wilfredo; suliman, Sara; Fulcher, Isabel; Molano, Francisco; Collins, Shannon; Uceta, Elizabeth; Zhu, Jack; Paxton, Ryan; Gonsalves, Sean; Harden, Maegan; Fisher, Marissa; Meldrim, Jim; et al.
Abstract: Background: Point-of-care antigen-detecting rapid diagnostic tests (RDTs) to detect Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) represent a scalable tool for surveillance of active SARS-CoV-2 infections in the population. Data on the performance of these tests in real-world community settings will be paramount for their implementation to combat the COVID-19 pandemic. Methods: We evaluated the performance characteristics of the CareStart TM COVID-19 Antigen Test (CareStart) in a community testing site in Holyoke, Massachusetts. We compared CareStart to a SARS-CoV-2 reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) reference, both using anterior nasal swab samples. We calculated the sensitivity, specificity, and the expected positive and negative predictive values at different SARS-CoV-2 prevalence estimates. Results: We performed 666 total tests on 591 unique individuals. 573 (86%) were asymptomatic. There were 52 positive tests by RT-qPCR. The sensitivity of CareStart was 49.0% (95% Confidence Interval (CI): 34.8 – 63.4) and specificity was 99.5% (95% CI: 98.5 – 99.9). Among positive RT-qPCR tests, the median cycle threshold (Ct) was significantly lower in samples that tested positive on CareStart. Using a Ct less than or equal to 30 as a benchmark for positivity increased the sensitivity of the test to 64.9% (95% CI: 47.5 – 79.8). Performance characteristics of CareStart test results benchmarked against the RT-qPCR gold standard (excluding undetermined results). Examples of images of CareStart rapid test showing variable band intensities. N2 gene RT-qPCR Cycle threshold (Ct) values corresponding to positive and negative CareStart rapid antigen test results for all RT-qPCR positive samples (n=52). Conclusion: Our study shows that CareStart has a high specificity and moderate sensitivity. The utility of RDTs, such as CareStart, in mass implementation should prioritize use cases in which a higher specificity is more important, such as triage tests to rule-in active infections in community surveillance programs. Disclosures: All Authors : No reported disclosures